Determinants of Economic Growth, Poverty, and Unemployment: A Path Analysis Study - Iwan Harsono; I Gusti Ayu Purnamawati; Ida Wayan Demung (Jurnal Ilmu Sosial dan Humaniora, 2023)
The main objective of this study is to reveal the role of regional own-source revenues, development spending, and regional minimum wages for economic growth, poverty, and unemployment in this research. A quantitative approach with path analysis was used in this study, which was in Cities and Regencies in Bali Province for the 2015-2021 period. A sample of 62 was analyzed using multiple linear regression methods. The results of the study state that Original Local Government Revenue (PAD), development expenditures, and regional minimum wages have a significant and positive effect on economic growth. PAD and regional minimum wages have a significant and positive effect on poverty, and development spending has a significant and negative effect. PAD does not affect unemployment. Development spending and regional minimum wages significantly and positively affect unemployment.